Correlation of bone age, dental age, and chronological age in survivors of childhood acute lymphoblastic leukaemia - MARY BETH MARTIN, CHIN-SHANG LI, CHRISTOPHER C. ROWLAND, SCOTT C. HOWARD, & SUE C. KASTE (IAPD and Blackwell)
Delay in growth and development represents established sequelae of treatment for childhood acute lymphoblastic leukaemia (ALL),but little information is available as to the potential effect of early age oncotherapy on dental development.